Faktor kesulitan membaca pemahaman teks cerita bahasa jawa peserta didik kelas V Sekolah Dasar - Siti Aminah Nur hidayah; Joko Daryanto; Idam Ragil Widianto Atmojo (Didaktika Dwija Indria, 2024)
This research is motivated by observation and interview data which indicate there are problems at school regarding the low reading comprehension skills of fifth grade students at SDN Tegalayu Surakarta in the 2022/2023 academic year. To overcome these problems, the researcher conducted a qualitative study with the aims of: (1) To describe the difficulties in understanding Javanese texts (2)to explain the factors that cause difficulties in understanding Javanese texts.This research was conducted on teachers and students of class V SDN Tegalayu Surakarta. In this research, a qualitative descriptive approach was used, and observation, interviews, and documentation studies were used to collect data.Source triangulation and triangulation techniques are used to test the validity of the data.From the research, data were obtained in the form of difficulties experienced by students, namely difficulties in interpreting words, difficulties in making new sentences using words in the text of the story and difficulty answering questions according to the contents of the story. While the factors that affect the difficulty of reading comprehension skills are intellectual factors, psychological factors, environmental factors and physiological factors.